Training-induced adaptation in purine metabolism in high-level sprinters vs. triathletes - Zielinski, J.; Kusy, K. (Journal of Applied Physiology, 2012)
The aim of this study was to assess the effect of training loads on metabolic response of purine derivatives in highly trained sprinters (10 men, age range 20-29 yr) in a 1-yr cycle, compared with endurance-training mode in triathletes (10 men, age range 21-28 yr). A four-time measurement of respiratory parameters, plasma hypoxanthine (Hx) concentration, and erythrocyte hypoxanthine-guanine phosphoribosyl transferase (HGPRT) activity was administered in four characteristic training phases (general, specific, competition, and transition). A considerably lower postexercise plasma concentration of Hx in sprinters (8.1-18.0 µmol/l) than in triathletes (14.1-24.9 µmol/l) was demonstrated in all training phases. In both groups, a significant decrease in plasma Hx concentration in the competition phase and a considerable increase in the transition phase were observed. It was found that the resting erythrocyte HGPRT activity increased in the competition period and declined in the transition phase. Sprinters showed higher HGPRT activity (58.5-71.8 nmol IMP/mg Hb·h) than triathletes (55.8-66.6 nmol IMP/mg Hb·h) in all examinations. The results suggest a more effective use of anaerobic metabolic energy sources induced by sprint training characterized by higher amount of exercise in the anaerobic lactacid and the nonlactacid zone. The changes in plasma Hx concentration and erythrocyte HGPRT activity might serve as sensitive metabolic indicators in the training control, especially in sprint-trained athletes. These parameters may provide information about the energetic status of the muscles in highly trained athletes in which no significant adaptation changes are detected by means of commonly acknowledged biochemical and physiological parameters.